Tussen de zichtbare en de onzichtbare wereld: over vrijmetselaarsfilosofie en Mozart - Commers, Ronald 1946- (Leuven Acco, 2008)
This book aims to give a very different view of the genesis and development history of Freemasonry. The main thesis is that the transition from craft guilds, called operative lodges, to speculative lodges is a quagmire. The roots and stem of European Freemasonry are philosophical and spiritual. Freemasonry is indebted to the worldview innovations associated with Renaissance philosophy and the Radical Reformation. In its essence it is as much continental as it is Anglo-Saxon or Scottish. The crowning achievement of that speculative Freemasonry is the lived spiritual testimony that can be heard in Mozart's music. (Translated with DeepL.com)
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Freemasonry; Cultural history; Philosophy